EFEKTIVITAS INTERVENSI PSIKO-EDUKASI BERBASIS HEATLH BELIEVE MODEL (HBM) DALAM MENINGKATKAN SELF EFFICACY PENGOBATAN TB MDR - Dewi, Dewi; Rayasari, Fitran; Anggraini, Dewi; Hasanah, Uswatun (Edu Masda Journal, 2025)
ABSTRACTBackground: Multidrug-Resistant (MDR) Tuberculosis (TB) is a global health problem that demands innovative approaches to improve treatment adherence and treatment outcomes. Objectives: This study evaluates the effectiveness of an independent nursing intervention that combines psychological counseling and education based on the Health Belief Model (HBM) on the self-efficacy and treatment compliance of MDR TB patients at Persahabatan Hospital. Method: A quasi-experimental method with a control group design and pre-test post-test was used on a sample of 32 patients, divided into intervention and control groups. Results: showed a significant reduction in non-adherence rates in the intervention group from 19.4% to 9.5%, while the control group experienced an increase from 19.4% to 24.4%. Statistical analysis showed a significant difference between the two groups (AOR = 0.31, 95% CI [0.18-0.53], p<0.001), indicating that the intervention was successful in increasing medication adherence. These findings emphasize the importance of integrating psychosocial approaches in the management of MDR TB to improve treatment adherence. Conclusion: This study provides empirical evidence of the effectiveness of HBM-based interventions in improving self-efficacy and treatment adherence, recommending their adoption in routine TB treatment strategies.                                                ABSTRAKTuberculosis (TB) Multidrug-Resistant (MDR) adalah masalah kesehatan global yang menuntut pendekatan inovatif untuk meningkatkan kepatuhan pengobatan dan hasil pengobatan. Penelitian ini mengevaluasi efektivitas intervensi keperawatan mandiri yang menggabungkan konseling psikologis dan edukasi berbasis Health Belief Model (HBM) terhadap self-efficacy dan kepatuhan pengobatan pasien TB MDR di RSUP Persahabatan. Metode quasi-eksperimental dengan desain kelompok kontrol dan pre-test post-test digunakan pada sampel sejumlah 32 pasien, dibagi menjadi kelompok intervensi dan kontrol. Hasil menunjukkan penurunan signifikan dalam tingkat ketidakpatuhan pada kelompok intervensi dari 19,4% menjadi 9,5%, sementara kelompok kontrol mengalami peningkatan dari 19,4% menjadi 24,4%. Analisis statistik menunjukkan perbedaan yang signifikan antara kedua kelompok (AOR = 0.31, 95% CI [0.18-0.53], p<0.001), menandakan bahwa intervensi berhasil meningkatkan kepatuhan pengobatan. Temuan ini menegaskan pentingnya integrasi pendekatan psikososial dalam pengelolaan TB MDR untuk meningkatkan kepatuhan pengobatan. Penelitian ini memberikan bukti empiris tentang efektivitas intervensi berbasis HBM dalam meningkatkan self-efficacy dan kepatuhan pengobatan, merekomendasikan adopsinya dalam strategi pengobatan TB rutin.